p95-HER2 and trastuzumab resistance in metastatic breast cancer; is immunohistochemistry appropriate? - (:unkn) unknown (IMPRIMATUR PUBLICATIONS, 2014)
Purpose: Unraveling the mechanisms underlying the resistance to trastuzumab is important for amending the prognosis of patients with human epidermal growth factor receptor 2 (HER2) positive metastatic breast cancer. Experimentally, it has been shown that p95-HER2 positive breast tumors are resistant to trastuzumab. The aim of this study was to investigate the predictive and prognostic importance of p95-HER2 expression by immunohistochemistry in HER2-positive metastatic breast cancer patients treated with trastuzumab. Methods: Only patients who had a histological diagnosis of HER2-positive metastatic breast cancer and who had received first line therapy containing trastuzumab were enrolled in the study. Immunohistochemistry was used to analyze p95-HER2 expression in the tissue blocks of the patients. Results: The study was performed on 38 patients aged between 30 and 84 years. In 14 patients (36.8%), p95-HER2 was positive, whereas it was negative in the remaining 24 patients (63.2%). There was no significant correlation between p95-HER2 expression and overall survival, response to trastuzumab, and progression-free survival (PFS). Conclusion: Unlike previous reports, there was no correlation between the p95-HER2 expression and resistance to trastuzumab. It may be argued that an analysis using immunohistochemistry is inadequate for determining p95-HER2. In order to ascertain whether immunohistochemistry is an appropriate method, studies with larger patient groups are needed. `
Keywords: breast cancer; HER2; p95-HER2; trastuzumab; EXTRACELLULAR DOMAIN; MONOCLONAL-ANTIBODY; RECEPTOR; CLEAVAGE; P95HER2; PROTEIN; GROWTH